Synthesis and characterization of a cyclometallated palladium(II) complex with (2-diphenylphosphino)ethylamine. (27th May 2019) - Elsegood, Mark R. J.; Han, Jiabao; Smith, Martin B.; Wu, Shimeng
Abstract: Reaction of commercially available Ph2 PCH2 CH2 NH2 with {PdCl(C9 H12 N)}2 (2:1) in CH2 Cl2 afforded, instead of Pd(Cl)( P -Ph2 PCH2 CH2 NH2 )(C9 H12 N) 1, the cationic complex [Pd( P, N -Ph2 PCH2 CH2 NH2 )(C9 H12 N)]Cl 2 which was characterized by single crystal X-ray crystallography. The lack of reactivity of 2 towards Rhodamine 6G can therefore be rationalized. Graphical Abstract: UF0001